Tetraselmis suecica and Porphyridium cruentum exopolysaccharides show anti-VHSV activity on RTG-2 cells - Parra-Riofrio, Geovanna; Moreno, Patricia; García-Rosado, Esther; Alonso-Sánchez, María del Carmen; Uribe-Tapia, Eduardo; Abdala-Díaz, Roberto Teófilo; Béjar-Alvarado, Julia (Springer, 2023)
The use of functional feed additives is an important approach to both, prevent and fight, viral diseases in aquaculture. In this regard, microalgae-derived products, and, more specifically, microalgal exopolysaccharides (EPSs), have attracted attention, since multiple biotechnological applications are being described for these molecules. Furthermore, depending on culture conditions, the composition and, therefore, properties of EPSs can vary. In the present study, the antiviral activity of EPSs from Tetraselmis suecica and Porphyridium cruentum cultured under autotrophic and heterotrophic conditions has been evaluated in vitro against Viral Haemorrhagic Septicaemia Virus (VHSV), an important pathogen in fish farming. Results showed that EPSs from both species have anti-VHSV activity. T. suecica EPSs from autotrophic cultures showed the strongest effect, since both, adsorption and post-adsorption phases of the VHSV multiplication cycle were affected. In contrast, both, autotrophic and heterotrophic P. cruentum EPSs showed anti-VHSV activity only after the adsorption phase. These results pave the way to use these EPSs to fight VHSV infections, and animate to evaluate the EPS antiviral activity against other viral pathogens relevant to the aquaculture industry.
Keywords: Agentes antivíricos; Exopolisacáridos microbianos; Tetraselmis; Porphyridium; VHSV; Antiviral activity; Exopolysaccharides